245 Effects of dietary macronutrient content on fecal microbiota populations and metabolite concentrations of healthy adult dogs. (5th December 2019) - Lin, Ching-Yen; Carroll, Meredith; Yang, Xiaojing; Do, Sungho; Shi, Wanting; Phungviwatnikul, Thunyaporn; He, Fei; Swanson, Kelly S
Abstract: Diet is one of the greatest influences on gut microbiota number and activity, and one that can rapidly alter conditions. However, limited information about the longitudinal effects of diet on canine fecal microbiota is available. The objective of this study was to determine the effects of dietary macronutrient content on fecal microbiota populations and metabolites of adult dogs. Twelve adult female beagles (age: 5.16±0.87 yr, BW: 13.37±0.68 kg) were used in a crossover design with two 27-d experimental periods. All dogs were fed a kibble diet (control) from d1–14, and then fed that diet supplemented with fiber (HFD) or changed to a canned diet (CD) from d15–27. Fresh fecal samples were collected on d13, 16, 20, 24, and 27 for measurement of metabolites and microbiota populations. Microbial data were analyzed using QIIME 2. Other data were analyzed using Mixed Models procedure of SAS 9.4. Compared with controls, dogs fed HFD had greater (P < 0.05) daily fiber intake, while dogs fed CD had greater (P < 0.05) daily protein and fat intakes. Fecal acetate, propionate, and total SCFA increased (P < 0.05) after the change to HFD (d16), with concentrations being maintained through d27. Fecal isobutyrate, isovalerate, total BCFA, phenol, and indole increased (P < 0.05) after dogs consumed CD (d16), with concentrations being maintained through d27. When dogs consumed HFD (d16), microbial alpha-diversity increased (P < 0.05) and was maintained through d27, while beta-diversity (weighted UniFrac distance measures) were altered (P < 0.05) and stabilized from d20 to d27. Relative abundances of Firmicutes increased (P < 0.05) by d24, while Fusobacteria decreased (P < 0.05) by d16 and was stable from d20 to d27, in dogs fed HFD. In conclusion, diets affected fecal microbiota and metabolites. Although concentrations of fecal metabolites were stabilized after 2d, fecal microbial populations needed more time to stabilize after diet transition.